Considering Value in Rectal Cancer Surgery: An Analysis of Costs and Outcomes Based on the Open, Laparoscopic, and Robotic Approach for Proctectomy. Issue 5 (May 2017) - Silva-Velazco, Jorge; Dietz, David W.; Stocchi, Luca; Costedio, Meagan; Gorgun, Emre; Kalady, Matthew F.; Kessler, Hermann; Lavery, Ian C.; Remzi, Feza H.
Abstract : Objective: The aim of the study was to compare value (outcomes/costs) of proctectomy in patients with rectal cancer by 3 approaches: open, laparoscopic, and robotic. Background: The role of minimally invasive proctectomy in rectal cancer is controversial. In the era of value-based medicine, costs must be considered along with outcomes. Methods: Primary rectal cancer patients undergoing curative intent proctectomy at our institution between 2010 and 2014 were included. Patients were grouped by approach [open surgery, laparoscopic surgery, and robotic surgery (RS)] on an intent-to-treat basis. Groups were compared by direct costs of hospitalization for the primary resection, 30-day readmissions, and ileostomy closure and for short-term outcomes. Results: A total of 488 patients were evaluated; 327 were men (67%), median age was 59 (27–93) years, and restorative procedures were performed in 333 (68.2%). Groups were similar in demographics, tumor characteristics, and treatment details. Significant outcome differences between groups were found in operative and anesthesia times (longer in the RS group), and in estimated blood loss, intraoperative transfusion, length of stay, and postoperative complications (all higher in the open surgery group). No significant differences were found in short-term oncologic outcomes. Direct cost of the hospitalization for primary resection and total direct cost (including readmission/ileostomy closure hospitalizations) were significantly greater in the RS group. Conclusions: The laparoscopic and open approaches to proctectomy in patients with rectal cancer provide similar value. If robotic proctectomy is to be widely applied in the future, the costs of the procedure must be reduced.